Inserção Internacional do Reino Unido: a utilização das Indústrias Criativas a partir da década de 1990 - Lohmann, Milena Adrieli (Universidade do Vale do Rio dos Sinos, 2022)
The 21st century has been marked by many changes in the most diverse aspects of human life. From the popularization of radio to the invention of the Internet, advances in information technology have impacted the relationship between individuals and the way knowledge, customs, and ideas are transmitted. In this context, societies and the international system have also changed, to the point that theorists consider the emergence of an information society, or knowledge society. Emerging alongside these changes, globalization has also brought its impact, generating, among its many effects, the displacement of industries. Thus, pioneering countries in the industrial field, such as the United Kingdom, began to face a progressive reduction in this sector, which historically has been fundamental to their international insertion. It is in this context of cultural change that the creative industries emerge, as a response to the socioeconomic framework of deindustrialization. Since their rise, the creative industries have been conquering more and more space in international discussions, arousing the interest of countries and international organizations. When it comes to these industries, the case of the United Kingdom is the reference for its pioneering association of the theme to a political and economic agenda. Given this scenario, this work is presented as exploratory research with a qualitative approach, which used mainly secondary sources to present the United Kingdom's creative industries and their role in the country's international insertion since the 1990s, when the term "Creative Industries" was coined. Throughout the research, information gathered from available bibliographical sources proved the important positive effects of the creative industries on the United Kingdom's international insertion. In this sense, the creative industries collaborate with the international insertion of the United Kingdom by 1) promoting a positive image of the country; and 2) being characterized as one of the most important industrial sectors of the United Kingdom.
Keywords: Inserção Internacional; Indústrias Criativas; Reino Unido; Globalização; International Insertion; Creative Industries; United Kingdom; Globalization